Microleakage assessment of pit and fissure sealant with and without the use of pumice prophylaxis - G. ANSARI, K. OLOOMI, & B. ESLAMI (Paediatric Dentistry, 2004)
This study evaluated the effect of pumice prophylaxis on the level of microleakage around and between the sealant and enamel.